2009
DOI: 10.1148/radiol.2532081390
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Stage T1c Prostate Cancer: Evaluation with Endorectal MR Imaging and MR Spectroscopic Imaging

Abstract: Purpose:To assess the diagnostic accuracy of endorectal magnetic resonance (MR) imaging and MR spectroscopic imaging for prediction of the pathologic stage of prostate cancer and the presence of clinically nonimportant disease in patients with clinical stage T1c prostate cancer. Materials and Methods:The institutional review board approved-and waived the informed patient consent requirement for-this HIPAAcompliant study involving 158 patients (median age, 58 years; age range, 40 -76 years) who had clinical sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 44 publications
2
42
0
1
Order By: Relevance
“…Subtle signs of EPE used in standardised reporting systems include: extent of contact of the tumour with the capsule, loss of the recto-prostatic angle, bulging or irregularity of the 'pseudo-capsule' , reduced signal in the peri-prostatic fat and asymmetry of the neurovascular bundle; these signs can increase the accuracy of MRI in detecting EPE to 77%-80% [110,111]. The main limitation of MRI in T-staging is limited sensitivity, due to its inability to detect microscopic EPE.…”
Section: Mri In T-staging Treatment Selection and Planningmentioning
confidence: 99%
“…Subtle signs of EPE used in standardised reporting systems include: extent of contact of the tumour with the capsule, loss of the recto-prostatic angle, bulging or irregularity of the 'pseudo-capsule' , reduced signal in the peri-prostatic fat and asymmetry of the neurovascular bundle; these signs can increase the accuracy of MRI in detecting EPE to 77%-80% [110,111]. The main limitation of MRI in T-staging is limited sensitivity, due to its inability to detect microscopic EPE.…”
Section: Mri In T-staging Treatment Selection and Planningmentioning
confidence: 99%
“…Researchers in numerous studies have suggested that magnetic resonance (MR) imaging, used alone or in combination with functional or metabolic MR imaging techniques, such as MR spectroscopic imaging, can contribute valuable information to the pretreatment assessment of prostate cancer (4,(11)(12)(13)(14)(15)(16)(17)(18). Therefore, the purpose of our study was to prospectively evaluate the diagnostic performance of T2-weighted MR imaging and MR spectroscopic imaging in detecting lesions stratified by pathologic volume and Gleason score in men with clinically determined low-risk prostate cancer.…”
Section: Genitourinary Imaging: Mr Performance Characteristics In Lowmentioning
confidence: 99%
“…Between December 2005 and November 2009, 358 patients gave informed consent to be enrolled in a prospective Institutional Review Board-approved National Institutes of Health study investigating the use of pretreatment MR imaging and MR spectroscopic imaging for assessing clinically low-risk prostate cancer (clinical stage T1c-T2a, Gleason than expected (3,4). Conversely, many patients with clinically low-risk prostate cancer harbor clinically insignificant disease that may never require treatment (5).…”
Section: Patientsmentioning
confidence: 99%
“…4), seminal vesicles, bladder wall, and local lymph nodes ( Fig. 5) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). It should be noted, however, that MRI generally underestimates nodal involvement because it relies on nodal enlargement.…”
Section: Clinical Roles Of Prostate Mri Mri For Local Staging After Amentioning
confidence: 99%